The study of the informal city using the sources available: the case of illegal urbanisations in Andalusia - López-Casado, David (Revista de Estudios Andaluces, 2022)
The phenomenon of illegal urbanisations continues to be one of the great environmental and territorial challenges to be overcome in Andalusia. In spite of this, the process of fully understanding this phenomenon is significantly hindered by the scarcity of easily accessible sources that allow the scientific community to study and analyse them. This article focuses on highlighting, firstly, the scarcity of existing sources for the study of illegal urbanisations on intermediate scales; and, secondly, when they exist, their limitations to allow a diachronic analysis of the process. In addition, the possibilities offered by other cartographic sources available in the region are explored. The results point to the need for the regional administration to update the inventories in order to know the current situation of the process, as well as the limitations and potential of the Spatial Reference Data for this purpose.